Mongolia's Challenge: Becoming Asian in Higher Education - Postiglione, Gerard (International Higher Education, 2010)
Despite the global economic crisis, the Republic of Mongolia is determined to move ahead in restructuring its higher education system. But, Government spending on higher education is severely limited in comparison to other regional players. Also, the quality of private higher education has yet to surpass that of the public institutions. The economy is currently too weak to support the large number of university graduates, and many are seeking employment elsewhere.